VEGF attenuated increase of outward delayed-rectifier potassium currents in hippocampal neurons induced by focal ischemia via PI3-K pathway. (9th July 2015) - Wu, K.W.; Yang, P.; Li, S.S.; Liu, C.W.; Sun, F.Y.
Highlights: Brain ischemia enhanced outward delayed-rectifier potassium current ( IK ). VEGF acutely and reversibly inhibited increase of IK by ischemic injury. VEGF inhibited ischemia-induced IK increase via PI3-K signaling pathway. Abstract: We recently indicated that the vascular endothelial growth factor (VEGF) protects neurons against hypoxic death via enhancement of tyrosine phosphorylation of Kv1.2, an isoform of the delayed-rectifier potassium channels through activation of the phosphatidylinositol 3-kinase (PI3-K) signaling pathway. The present study investigated whether VEGF could attenuate ischemia-induced increase of the potassium currents in the hippocampal pyramidal neurons of rats after ischemic injury. Adult male Sprague–Dawley rats were subjected to transient middle cerebral artery occlusion (MCAO) to induce brain ischemia. The whole-cell patch-clamp technique was used to record the potassium currents of hippocampal neurons in brain slices from the ischemically injured brains of the rats 24 h after MCAO. We detected that transient MCAO caused a significant increase of voltage-gated potassium currents ( Kv ) and outward delayed-rectifier potassium currents ( IK ), but not outward transient potassium currents ( IA ), in the ipsilateral hippocampus compared with the sham. Moreover, we found that VEGF could acutely, reversibly and voltage-dependently inhibit the ischemia-induced IK increase. This inhibitory effect of VEGF could be completely abolished by wortmannin, an inhibitor of PI3-K. Our data indicate that VEGF attenuates the ischemia-induced increase of IK via activation of the PI3-K signaling pathway.